The Cytotoxicity Effect for the Crude Extract of (Cyperus Esculentus) Tubers on Human Breast Cancer Cell Line (MCF-7) in Vitro - Zainab Abd Amir Mezher1 , Liqaa H. Saqban2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aimed to identify the aqueous and alcoholic extract of Cyperus esculentus tubers in affectinghuman breast cancer (MCF-7) Michigan Cancer Foundation,preliminary diagnosis chemical groups in theseextracts showed the presence of (Tannins, Terpenoids, Resins, Steroids, Flavonoids, Alkaloids, Glycosidesand Phenols). The effect of cellular toxicity of crude aqueous and alcoholic extract of Cyperus esculentustubers in vitro was tested in human breast cancer cells (MCF-7) through the use of six concentrations(midterm scares) (31.25,62.5,125,250,500,1000 ) ?g /mL and for periods of exposure (24, 48, 72) hours.Using the MTT Test. The study found that there is a toxic effect of the crude aqueous and alcoholic extractsof the grain of Cyperus esculentus tubers in cancer cells (MCF-7) and of all the concentrations used, Thehighest percentage and a significant difference (P ?0.01) for the average of the inhibitory average of cancercell growth (IR) was 68, 73 (%) for the aqueous extract and alcoholic extract, respectively, at the highestconcentration of 1000 ?g / mL and after 72 hours of exposure.